EQUIVALENT RELIABILITY POLYNOMIALS - Udrişte, C.; A. H. Hassan, Z.; Ţevy, I. (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2016)
Looking for geometric modeling of reliability polynomials, we discuss three important ideas: find equivalent reliability polynomials via diffeomorphisms; cover a reliability hypersurface by probability straight lines; cover a reliability hypersurface by exponential decay curves. In this paper we shall prove that two reliability polynomials, attached to some electric systems used inside aircrafts, are equivalent via an algebraic diffeomorphism. Also, we introduce the X-loxodromic curves on an equi-reliable hypersurface, which are constrained paths (evolutions) that are equi-reliable.